Assessment of physician-patient relationships at the obstetrics and gynecology departments - Chilicka, Magdalena; Krajewska-Kułak, Elżbieta; Rozwadowska, Emilia; Terlikowski, Robert; Hładuński, Marcin; Izabela Młynarczyk, Izabela Młynarczyk (Nursing in the 21st Century, 2011)
Introduction. Current system of the health care makes patient become the active and evaluative client of medical services recommended by the institution. Aim. The assessment of patients’ trust in their physicians at the obstetrics and gynecology departments. Material. Data were collected from 150 women hospitalized at the obstetric and gynecology departments. The scale of the trust in physician includes 11 questions. The patient should give answers according to five-score scale: 1-strongly disagree, 2-disagree, 3-neutral (neither disagree or agree), 4- agree, 5- strongly agree. Results: From among the studied patients 23.3% did not doubt about a proper doctor’s care. Fifty-nine percent of patients agreed that physician usually considers the needs of examined patients and places them in the first place. More than 90% of the respondents agreed with the statement „I trust my doctor very much, that is why I always comply to her/his advice”. Almost 68.7% of patients confirmed the statement: „if my physician tells something this always has to be the truth” Nearly 77.3% of the respondents declared the trust in their physician’s therapy. Almost 84% of patients were convinced that their doctor is a true expert in treating diseases. Thus 96.7% of patients did not declare fear of disclosing by physician the professional secrecy. Conclusions. Most patients doubted about appropriate doctor’s care at the obstetric and gynecology departments. The respondents trusted their physicians, that their needs were in the first place. They believed that physicians are always telling the truth, they are experts in the therapy of their ailments, and they keep the secrecy of their therapy.